2019
DOI: 10.1111/irv.12704
|View full text |Cite
|
Sign up to set email alerts
|

Influenza in patients with cancer after 2009 pandemic AH1N1: An 8‐year follow‐up study in Mexico

Abstract: Background Immunosupressed patients are at high risk of influenza‐related complications. Influenza AH1N1 has been hypothesized to induce worse outcomes in patients with malignancies, but after the A(H1N1)pdm09 few publications have analyzed the presentation and complications related to influenza afterward. Objectives We aimed to describe the characteristics, risk factors, and outcomes of influenza in an oncologic center after the 2009 pandemic and to compare our case distribution to the National community acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
(130 reference statements)
4
8
0
Order By: Relevance
“…In contrast to our findings, a study of over 2 million elderly individuals reported that those with dementia and no diabetes surprisingly had a lower frequency of influenza infections and a shorter length of stay in the hospital [28]. In our study, the diagnosis of cancer also increased the likelihood of IRI hospitalization, which is in line with previous research [29]. Within the group of people with diabetes and cancer, it is almost impossible to assess whether cancer per se or its pharmacotherapy increases the infection risk and mortality rate following an IRI.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to our findings, a study of over 2 million elderly individuals reported that those with dementia and no diabetes surprisingly had a lower frequency of influenza infections and a shorter length of stay in the hospital [28]. In our study, the diagnosis of cancer also increased the likelihood of IRI hospitalization, which is in line with previous research [29]. Within the group of people with diabetes and cancer, it is almost impossible to assess whether cancer per se or its pharmacotherapy increases the infection risk and mortality rate following an IRI.…”
Section: Discussionsupporting
confidence: 87%
“…Cancer patients with the A(H1N1) flu have similar symptoms as the general population, but tend to have haematological abnormalities as anaemia, neutropenia or leukopenia[ 32 ]. Different clinical series described that patients with solid or haematological tumours had a poor prognosis during the pandemic, such as increased hospitalization, bacterial infection, and death[ 33 - 36 ]. In fact, it has been described that patients who received chemotherapy in the last month or had neutropenia on admission had fatal outcomes[ 33 , 35 ].…”
Section: Cancer Patients In Pandemicmentioning
confidence: 99%
“…2 Influenza generally achieves community spread nationwide and can strike all age groups, but mortality is consistently higher in patients who are elderly, immunocompromised, and/or have pre-existing comorbidities such as chronic obstructive pulmonary disease, chronic kidney injury, cirrhosis, or cardiac disease. [3][4][5][6][7][8][9] Decades of experience with influenza have led to vaccination programs which can mitigate the impact of influenza in years when the predominant circulating strain is accurately predicted. 10 Official CDC counts indicate that over one million people in the USA have contracted COVID-19 between the virus's first detected cases through April 30, 2020, with over 150,000 hospitalizations and over 63,000 deaths reported as of that date.…”
Section: Introductionmentioning
confidence: 99%